Pathogenicity of Indigenous Entomopathogenic Fungi from West Sumatera, Indonesia, against Fall Armyworm Spodoptera frugiperda and Their Effects on Post-Larval Development - Trizelia Trizelia; Haliatur Rahma; Yusniwati Yusniwati; Indri Yanil Vajri (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2026)
Spodoptera frugiperda is a major invasive pest of maize that requires effective control strategies. Entomopathogenic fungi are promising biological control agents because they can infect larvae and disrupt insect development. However, information on indigenous fungal isolates from West Sumatra, Indonesia remains limited. Moreover, their effects on post-larval development of S. frugiperda are still poorly understood. This study aimed to evaluate the pathogenicity of several fungal isolates against S. frugiperda under laboratory conditions. The experiment was arranged in a Completely Randomized Design (CRD) with eight treatments and four replications. The treatments consisted of six fungal isolates (Beauveria bassiana BBWS, B. bassiana BBPD, Metarhizium anisopliae B22C, M. anisopliae KRJ, Trichoderma asperellum A116, T. asperellum S2D11) and two controls (sterile distilled water and cypermethrin). Fungal suspensions were applied to second-instar larvae at 1 × 10⁸ conidia mL⁻¹. All data were analyzed using ANOVA followed by the LSD test at the 5% level. This study showed that the entomopathogenic fungal isolates tested affected the survival and postlarval development of S. frugiperda under laboratory conditions. The fungal treatments caused larval mortality ranging from 40 - 70% and reduced the proportion of larvae into the pupal and adult stages. Among the tested isolates, B. bassiana BBWS was the most effective, causing the highest larval mortality, the shortest LT₅₀, and the lowest pupal and adult formation. However, further research is needed to confirm the pathogenicity mechanisms of the isolates, their conidial viability and stability during storage, and their efficacy under greenhouse and field conditions.